Penerapan Sistem Bagi Hasil Produk Tabungan Mudharabah Bank Riau Kepri Syariah Tembilahan - Veni Lestari; Sai'in Sai'in (STAI Auliaurrasyidin Tembilahan, 2022)
This study aims to find out how the application of the profit-sharing system for mudharabah savings products at Bank Riau Kepri KCP Tembilahan. This type of qualitative research with purposive sampling technique consisting of 4 employees and 4 customers. Interview and documentation data collection techniques as well as data analysis techniques consist of reduction, display and verification as well as drawing conclusions. The results showed that the implementation of the profit-sharing system for iB mudharabah savings products at Bank Riau Kepri Syariah when viewed from the agreement, profit ratio, cooperation, transparency, timeliness, and profit was appropriate, even though the process of notifying the amount of profit sharing every month was not carried out and determining the profit ratio iB mudharabah savings products are not carried out with customers of savings products. Based on the results of the study it can be concluded that the application of a partial profit-sharing system for mudharabah savings products at Bank Riau Kepri Syariah KCP meets the profit-sharing indicators, the calculation system uses a revenue sharing system with the HI-1000 method, namely a calculation system per 1000 customer funds.